The Relationship between Cultural Intelligence and Psychological Well-being with the Moderating Effects of Mindfulness: A Study of International Students in Taiwan - Tzu-Ping, Yang; Chang, Wei-Wen (European Journal of Multidisciplinary Studies, 2022)
According to Ministry of Education of Taiwan, numbers of international students studying in Taiwan gradually increased. However, studies showed that their learning outcome is significantly influenced by their psychological well-being (PWB). Therefore, this study examines the factors affecting PWB. In this study, cultural intelligence (CQ) is seen as a potential predictor for PWB. CQ is defined as the ability to deal with different cultural context, and it includes four dimensions, namely cognitive CQ, metacognitive CQ, motivational CQ and behavioral CQ. Besides, as people pay more attention to unfamiliar exotic things when being abroad, their consciousness on the present moment, so-called mindfulness, plays an important role for their well-being. Therefore, mindfulness is examined as a moderator in the relationship between CQ and PWB. Quantitative approach is applied in this study. The samples are 110 international students studying in Taiwan. The self-report questionnaire composed by Ryff’s 18-item scale, Cultural Intelligence Scale and Mindful Attention Awareness Scale is distributed on-line. The collected data go through descriptive analysis, correlation analysis and regression analysis. Results show that metacognitive CQ and PWB has a significant relationship with an R2 of .231. Besides, motivational CQ is positive related to PWB with an R2 of .142. According to the statistic result of this study, future research can put efforts on how to enhance metacognitive and motivational CQ, like designing related cultural program courses before students’ departure, in order to better international students’ PWB.